Esophagogastric junction distensibility assessed using the functional lumen imaging probe - Chen, Joan W; Rubenstein, Joel H (World journal of gastroenterology : WJG, 2017)
AIM To assess reference values in the literature for esophageal distensibility and cross-sectional area in healthy and diseased subjects measured by the functional lumen imaging probe(FLIP). METHODS Systematic search and review of articles in Medline and Embase pertaining to the use of FLIP in the esophagus was conducted in accordance with the PRISMA guidelines. Cross-sectional area and distensibility at the esophagogastric junction(EGJ) were abstracted for normal subjects, achalasia, and gastroesophageal reflux disease(GERD) patients, stratified by balloon length and volume of inflation.RESULTS Six achalasia studies(n = 154), 3 GERD(n = 52), and 5 studies including healthy controls(n = 98) were included in the systematic review. Normative data varied widely amongst studies of healthy volunteers. In contrast, studies in achalasia patients uniformly demonstrated low point estimates in distensibility ≤ 1.6 mm2/mmH g prior to treatment that increased to ≥ 3.4 mm2/mmH g following treatment at 40 mL bag volume. In GERD patients, distensibility fell to the range of untreated achalasia(≤ 2.85 mm2/mm Hg) following fundoplication.CONCLUSION FLIP may be a useful tool in assessment of treatment efficacy in achalasia. The drastic drop in EGJ distensibility after fundoplication suggests that FLIP measurements need to be interpreted in the context of esophageal body motility and highlights the importance of pre-operative screening for dysmotility. Future studies using standardized FLIP protocol and balloon size are needed.